Reconciliation and Peacebuilding of Standup Comedy South Africa - Adekunle, Idowu James (Randwick International of Social Science Journal, 2024)
This study focuses on post-apartheid struggles and xenophobic attacks on non-South African Black nationals against the prior knowledge of racial discrimination between White and Black folks. Studies on post-apartheid struggles and xenophobic violence have widely been expressed via literature texts, neglecting the efficacy of stand-up comedy. Therefore, this study examines the efficacy of stand-up comedy in reconciliation and peace-building in post-apartheid struggles and xenophobic violence in South Africa. This study explores how comedians use empathetic narrative power of humour and performative techniques on-stage performance to foster unity, love, and peace among South African and non-South African nationals against killings, rape, violence, and deportation. Textual analysis of live recorded digital video of selected South African stand-up comedians and Schechner’s Performance and psychoanalytic theories of Freud and Jung were used to analyze the performance of the stand-up comedians and the success behind their outstanding popularity with their audiences.